Politik Anggaran dalam Penyusunan Dana Hibah Pilkada 2020 (Studi Kasus Kabupaten Karawang dan Kota Tangerang Selatan) - Elsa, Etika; Kosandi, Meidi (Indonesian Democracy Research Center, 2021)
This paper discusses budget politics in the 2020 local elections (Pilkada), focusing specifically on Karawang Regency and Tangerang Selatan City, with particular attention to the patterns of relationships among actors during the formulation and approval of Pilkada grant budgets in both regions. The study employs a qualitative research method, using in-depth interviews with officials and staff from election management bodies, local governments, and regional parliaments (DPRD). In practice, the findings reveal that although local leaders hold substantial power that could potentially allow them to manipulate, increase, or revoke budgetary decisions, they nevertheless adhered to the established budget cycle procedures and maintained a professional attitude throughout the process of allocating election grant funds.